Let eq= equilibrium

at eq, qd=qs

substitute qd= 15 - 1.5p and qs=p in the above derived equation to find the equilibrium price (P.e)

therefore, 15 - 1.5p = p

group like terms

-1.5p - p = -15

-2.5p = -15

make p the subject of the equation by dividing both side by -2.5

therefore,

-2.5p/-2.5 = -15/-2.5

p = 6

the equilibrium price (P.e) is 6

to find your equilibrium quantity you substitute 6 in any of the function. But not that the quantity will also be equal to 6 since the supply function (Qs) is equal to Price(P). This is illustrated below:

Qs= p

where p = 6

therefore,

Qs = 6

also you can use the demand function to confirm your answer. See below

Qd= 15 - 1.5p

where p = 6

therefore,

Qd = 15 - 1.5(6)

Qd= 15 - 9

Qd= 6

at eq, qd=qs

substitute qd= 15 - 1.5p and qs=p in the above derived equation to find the equilibrium price (P.e)

therefore, 15 - 1.5p = p

group like terms

-1.5p - p = -15

-2.5p = -15

make p the subject of the equation by dividing both side by -2.5

therefore,

-2.5p/-2.5 = -15/-2.5

p = 6

the equilibrium price (P.e) is 6

to find your equilibrium quantity you substitute 6 in any of the function. But not that the quantity will also be equal to 6 since the supply function (Qs) is equal to Price(P). This is illustrated below:

Qs= p

where p = 6

therefore,

Qs = 6

also you can use the demand function to confirm your answer. See below

Qd= 15 - 1.5p

where p = 6

therefore,

Qd = 15 - 1.5(6)

Qd= 15 - 9

Qd= 6